2017
DOI: 10.3748/wjg.v23.i47.8355
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin ameliorates hepatic encephalopathy and endotoxemia without affecting the gut microbiome diversity

Abstract: AIMTo determine the efficacy of rifaximin for hepatic encephalopathy (HE) with the linkage of gut microbiome in decompensated cirrhotic patients.METHODSTwenty patients (12 men and 8 women; median age, 66.8 years; range, 46-81 years) with decompensated cirrhosis (Child-pugh score > 7) underwent cognitive neuropsychological testing, endotoxin analysis, and fecal microbiome assessment at baseline and after 4 wk of treatment with rifaximin 400 mg thrice a day. HE was determined by serum ammonia level and number co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 45 publications
4
72
1
1
Order By: Relevance
“…Our study corroborates the findings of previous studies with no significant changes in overall gut microbiota composition in patients with MHE treated with rifaximin [9,26]. Furthermore, we were able to show that in parallel with the amelioration of symptoms, the gut microbiota composition remains stable also after the completion of rifaximin treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study corroborates the findings of previous studies with no significant changes in overall gut microbiota composition in patients with MHE treated with rifaximin [9,26]. Furthermore, we were able to show that in parallel with the amelioration of symptoms, the gut microbiota composition remains stable also after the completion of rifaximin treatment.…”
Section: Discussionsupporting
confidence: 82%
“…In patients with liver cirrhosis, rifaximin modulates the bacterial composition of the gut microbiota without a consistent effect on microbiota composition detected in the faeces [9,26]. Studies on changes in the duodenal microbiota composition of these patients have not been published so far.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of species of oral origin, such as Veillonella and Streptococcus , is reported to be high in the feces of cirrhotic patients . Rifaximin shows high antibacterial activity against Veillonella (minimal inhibitory concentration 50, 2 μg/mL) and Streptococcus (minimal inhibitory concentration 50, ≤0.03–0.12 μg/mL) and several studies have reported that RFX treatment decreases the relative abundances of the genera Veillonella and Streptococcus . Our findings on Streptococcus and Veillonella are in good agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…As RFX inhibits ammonia‐producing bacterial genera such as Clostridium and Streptococcus , it is thought to exert beneficial effects by modulating the bacterial composition of the gut microbiota . However, recent studies reported that treatment with RFX has only minor effects on intestinal bacterial composition in patients with decompensated liver cirrhosis and non‐alcoholic steatohepatitis . Thus, the effects of RFX on gut microbiota composition remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed whole blood endotoxin activity (EA) using the commercially available Endotoxin Activity Assay (EAA) kit (Spectral Diagnostics, Toronto, Canada), as described elsewhere . In brief, the EAA is based on the principle that endotoxin binds to antiendotoxin antibodies and is delivered to neutrophils by complement receptors.…”
Section: Methodsmentioning
confidence: 99%